An ethical crisis in ancient DNA research: Insights from the Chaco Canyon controversy as a case study. (June 2021) - Cortez, Amanda Daniela; Bolnick, Deborah A; Nicholas, George; Bardill, Jessica; Colwell, Chip
In recent years, the field of paleogenomics has grown into an exciting and rapidly advancing area of scientific inquiry. However, scientific work in this field has far outpaced the discipline's dialogue about research ethics. In particular, Indigenous peoples have argued that the paleogenomics revolution has produced a "vampire science" that perpetuates biocolonialist traditions of extracting Indigenous bodies and heritage without the consent of, or benefits to, the communities who are most affected by this research. In this article, we explore these ethical issues through the case study of a project that sequenced the ancient DNA (aDNA) of nine Ancestral Puebloan people from Chaco Canyon, New Mexico. By providing a "thick description" of this controversy, we are able to analyze its metanarratives, periodization, path dependency, and historical contingencies. We conclude that the paleogenomics revolution needs to include an ethical revolution that remakes the field's values, relationships, forms of accountability, and practices.